Association between dietary carbohydrates quality and nutritional status of prostate cancer survivors (Research, Society and Development, 2020)
The objective was to determine the carbohydrate quality index (CQI) of the diet of prostate cancer survivors, checking if there is an association with their nutritional status. This is a cross-sectional study, in which socio-demographic, anthropometric and food consumption data were collected from 106 male prostate cancer survivors. The CQI was determined as recommended in a specific protocol. The association between CQI and nutritional status (body mass index - BMI and waist circumference - WC) was assessed by Spearman's correlation test, with p